Dangerous [videorecording (DVD)] - Green, Alfred E., 1889-1960; Davis, Bette, 1908-1989; Tone, Franchot; Lindsay, Margaret, 1910-1981; Skipworth, Alison, 1863-1952; Eldredge, John, 1904-1961; Foran, Dick, 1910-1979 (Warner Home Video, 2012)
Joyce Heath falls in love with a new man, and tries to get rid of her husband.